2023
DOI: 10.1007/s00167-023-07612-8
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent repeatability of the Dejour classification of trochlear dysplasia due to the variability of imaging modalities: a systematic review

Tomas Pineda,
Jacobus Hendrik Müller,
Luca Nover
et al.

Abstract: Purpose The purpose of this systematic review was to critically assess the quality of papers that report on the intra-and inter-observer repeatability of the Dejour classification for trochlear dysplasia, and to identify the possible causes for poor repeatability. Methods Two authors independently conducted an electronic search (four databases) on 8 February 2023 for studies (English or French) that assessed trochlear dysplasia classifications on imaging of skeletally mature participants. Exclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Additionally, the cut‐off value of LP‐MEC could be determined to differentiate type A from types B, C and D. The elevated TG‐TEA and MP‐MEC in the proximal planes observed in types B and D indicated the prominence of morphological features previously identified in the dysplasia group: shallower trochlear depth and narrower medial trochlear width. This provides quantitative evidence to support the consideration of sulcus‐deepening trochleoplasty in patients of severe dysplasia, specifically types B and D, when supratrochlear measures >5 mm [13, 28]. Overall, our approach of quantifying multiple parameters across various patellar tracking angles in 3D analysis may be useful for differentiating between the four types of Dejour classification.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Additionally, the cut‐off value of LP‐MEC could be determined to differentiate type A from types B, C and D. The elevated TG‐TEA and MP‐MEC in the proximal planes observed in types B and D indicated the prominence of morphological features previously identified in the dysplasia group: shallower trochlear depth and narrower medial trochlear width. This provides quantitative evidence to support the consideration of sulcus‐deepening trochleoplasty in patients of severe dysplasia, specifically types B and D, when supratrochlear measures >5 mm [13, 28]. Overall, our approach of quantifying multiple parameters across various patellar tracking angles in 3D analysis may be useful for differentiating between the four types of Dejour classification.…”
Section: Discussionmentioning
confidence: 82%
“…Given the significant differences in TG-TEA and MP-MEC between the control and dysplasia groups, further comparative analyses were conducted after Abbreviations: LP-MEC, distance from the medial epicondyle (MEC) to the point on the transepicondylar axis (TEA) corresponding to the most cortical point of the lateral condyle; LP-TEA, distance from the TEA to the most cortical point of the lateral condyle, where LP is the lateral peak; MP-MEC, distance from the MEC to the point on the TEA corresponding to the most cortical point of the medial condyle; MP-TEA, distance from the TEA to the most cortical point of the medial condyle, where MP is the medial peak; TG-MEC, distance from the MEC to the point on the TEA corresponding to the deepest point of the trochlea; TG-TEA, distance from the TEA to the deepest point of the trochlea, where TG is the trochlear groove. [13,28]. Overall, our approach of quantifying multiple parameters across various patellar tracking angles in 3D analysis may be useful for differentiating between the four types of Dejour classification.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…MRI reveals certain features of the trochlear groove but misses the correlation with the lateral radiograph, which can give a full picture of the trochlea because of the superimposition of prominences [13]. Finally, a recent systematic review found that there is substantial variation, in the evidence base, regarding imaging protocols and nonstandardised criteria to distinguish dysplasia [22].…”
Section: Introductionmentioning
confidence: 99%
“…The misinterpretation or undervaluation of this condition can result in inappropriate or unsuccessful treatment. However, the analysis and classification of this condition are complex, posing a significant challenge for clinicians [2].Currently, only a few widely accepted classifications exist in the literature. Henri Dejour, in 1987, based his classification on the level of the crossing sign on lateral knee radiographs [3].…”
mentioning
confidence: 99%